DEVELOPMENT OF "ALIN GESIT" LEARNING MEDIA FOR COMPUTER ACCOUNTING SUBJECT - Hidayati, Khusnul; Rahmawati, Anis; Wijayanto, Danar Susilo (Assets: Jurnal Akuntansi dan Pendidikan, 2024)
ABSTRACT This research aimed to evaluate the feasibility of "Alin Gesit," a Google Sites-based learning media for online accounting computer courses. Using the ADDIE method, we analyzed student and teacher needs, designed and developed the media, and assessed it through expert evaluations and student-teacher feedback. The study involved twelfth-grade accounting students from a vocational school in East Java. Results showed that "Alin Gesit" scored 84% from media experts and 94% from material experts. A paired T-test (p=0.003) confirmed significant improvement in student scores. Additionally, students rated the media highly (3,7), indicating its effectiveness. ABSTRAK Penelitian ini bertujuan untuk mengevaluasi kelayakan "Alin Gesit", media pembelajaran berbasis Google Sites untuk kursus komputer akuntansi online. Dengan menggunakan metode ADDIE, kami menganalisis kebutuhan siswa dan guru, merancang dan mengembangkan media, dan menilainya melalui evaluasi ahli dan umpan balik siswa-guru. Penelitian ini melibatkan siswa akuntansi kelas dua belas dari sebuah sekolah kejuruan di Jawa Timur. Hasil penelitian menunjukkan bahwa "Alin Gesit" memperoleh nilai 84% dari ahli media dan 94% dari ahli materi. Uji-T berpasangan (p=0,003) mengkonfirmasi peningkatan signifikan dalam nilai siswa. Selain itu, siswa menilai media tersebut dengan tinggi (3,7), yang menunjukkan keefektifannya.